Classification of Target Markets and Features of Segmentation in Marketing Places - Praude, Valerijs; Vozņuka, Jekaterina (Ekonomika, 2008)
This paper examines target markets and the strategy of marketing places as an economic instrument directed to the development of countries, regions, cities and towns. The authors give a classification of potential target markets of a territory and their characteristics on an example of Latvia.Markets’ segmentation for realizing the strategy of marketing places is of great value as it allows concentrating activity on the most perspective directions of territory development and on methods of particular group attraction. It gives an opportunity to work with separate categories of consumers, to make marketing policy more direct and more expressive, to promote competitiveness of a territory and its social economic development.